Anatomical and Histological Analyses on Cattle and Horse Bones of Joseon Period Discovered at Archaeological Site in Old Seoul City Area. (28th February 2022) - Kim, Jieun; Hong, Jong Ha; Kim, Sun; Shin, Dong Hoon
Anatomical examination of animal bones found at archaeological sites can provide information that historical studies alone cannot. As related in this report, we performed morphological analyses on cattle and horse bones retrieved from Joseon-period ruins found at the Gongpyeongdong site (Seoul, South Korea). By anatomical and histological comparisons, we confirmed that the slaughter of Gongpyeongdong cattle and horses was done at a later age than is the case today. This was likely due to the fact that cattle and horses in Joseon society were raised primarily as beasts of burden and only secondarily for food; and so, the Joseon government strictly prohibited what it considered to be premature slaughter.